Percepção da escola-campo sobre o estágio supervisionado em Biologia: contribuições para uma avaliação curricular. - Sousa, Ana Lourdes Lucena de (2009)
This research project has as main purpose understanding supervised stage activities, under school manager’s and teacher´s point-of-view, seeing that they are responsible for the teachers-students reception at school. For one semester class period, the field-school was analyzed in its structure and action, as well as the supervised stage considering practical reflexive documental theory. Gestalt’s theory was used to comprehend the researched object that is the relationship between field-school and university reffering to a Biology major, through supervised stage. This work’s components are introduction and four chapters supplied in Franco and Ghedin’s (2008) Marleau Ponty’s (2006) Vianna´s (2000) Romanelli’s (2006) Fusary’s (1987) Pimenta and Lima’s (1993) studies, among others, beyond legal documents published by MEC and CNE. The research has based itself in the evaluative methodology, that can make possible the aggregation of the qualitative research procedures in the knowledge and learning construction. Both of these can give real mean to the study purpose reflection, analysis and evaluation. The qualitative research in phenomenological basis helped to understand data that has marked the space/time of the research. The most important results in this investigation are constituted by these points of reflection: the school managers and Biology teachers perception about supervised stage offered formative elements to the searcher, because they increased the learning field in education area and in the time spent inside public school. That was very important also for the teachers involved in this research through the opportunity of reflection, when they discussed their life experience. Biology teachers respect their knowledge area and hava Biology as The Science of Life. They also hope the teachers-students can help them encourage the students, because keeping the dialog is very difficult, when the class is disarticulated. The searcher marked her presence in the school, inviting to do a work involving school and university, that is an emergency. Teachers formation needs to increase the dialogue in the real spaces where it happens.